LIVER FUNCTIONS PROFILE OF TUBERCULOSIS PATIENTS IN INDONESIA DURING ANTITUBERCULOSIS TREATMENT - DA, PERWITASARI; D., SETIAWAN; T., SAFARIA; H., DANIA; IN, FARIDAH; LM, IRHAM (International Journal of Applied Pharmaceutics, 2024)
Objective: The objective of this study is to define the profile of liver function of tuberculosis patients during the treatment. Methods: We conducted the longitudinal study with adult tuberculosis patients treated with the first line of antituberculosis as the inclusion criteria. The pregnant and patients with comorbidities which related to liver function were excluded. We measured the total bilirubin, aspartate aminotransferase (AST), and alanine aminotransferase (ALT) over the 2nd, 4th, and 6th mo of the treatment. Results: We recruited 202 patients, with 58.91% male patients, and the mean age was 39.91 (SD: 17.18) years old. As 9% of tuberculosis patients experienced increased levels of bilirubin, AST, and ALT, and 50% among them experienced increased levels of bilirubin, AST, and ALT starting from 2nd mo of the treatment. The total bilirubin level in the 2nd,4th, and 6th mo were 0.57, 0.59 and 0.67 mg/dl, respectively. The AST levels were 27, 22, and 26 U/l in 2nd,4th and 6th mo, respectively, and the ALT levels were 21,19 and 25 U/l in 2nd,4th and 6th mo, respectively. At the end of the treatment, around 4.5% tuberculosis patients experienced high levels of bilirubin, AST and ALT. Conclusion: The monitoring treatment for tuberculosis patients should be conducted until the end of the treatment because the level of bilirubin, AST, and ALT increased after 6th mo of treatment.